2010
DOI: 10.1177/0146167210378111
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative and Career-Stage Citation Impact of Social-Personality Psychology Programs and Their Members

Abstract: Number of citations and the h-index are popular metrics for indexing scientific impact. These, and other existing metrics, are strongly related to scientists' seniority. This article introduces complementary indicators that are unrelated to the number of years since PhD. To illustrate cumulative and career-stage approaches for assessing the scientific impact across a discipline, citations for 611 scientists from 97 U.S. and Canadian social psychology programs are amassed and analyzed. Results provide benchmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 67 publications
(78 reference statements)
3
82
2
1
Order By: Relevance
“…This is reflected in the labeling of graduate programs: Of the major programs in social/personality in the United States and Canada listed in Nosek et al (2010) or the Social Psychology Network (2015), the majority (32 programs) include the label "social" without "personality." At 21 others, the terms are combined in a single area fused by ands, ampersands, hyphens, slashes, or (in one case) a vertical bar.…”
mentioning
confidence: 99%
“…This is reflected in the labeling of graduate programs: Of the major programs in social/personality in the United States and Canada listed in Nosek et al (2010) or the Social Psychology Network (2015), the majority (32 programs) include the label "social" without "personality." At 21 others, the terms are combined in a single area fused by ands, ampersands, hyphens, slashes, or (in one case) a vertical bar.…”
mentioning
confidence: 99%
“…These measures distinguish researchers who may have produced a few very highly cited articles from those who have produced a larger number of more moderately cited articles, an aspect of a researcher's citation profile that is missed by the h-index. In this regard, we note that Nosek et al (2010) created a database in which one can compare his or her h-and e-indices to those of 611 faculty members from various social-personality psychology Ph.D. programs who received their Ph.D.s at the same time as the person doing the query. We hope that an analogous database will be created for the subarea of cognitive psychology.…”
Section: Limitations Of the Present Approachmentioning
confidence: 99%
“…The number of citations that academic articles receive has become a well-accepted, objective measure for evaluating the impact (and likely the quality) of journals (Garfield, 1972), researchers, departments, programs, or institutions (Nosek et al, 2010;Rushton, 1984). A very high citation rate for a published article indicates that the research it reports has had a major impact in guiding the research reported in other articles in that field.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we illustrate use of the programs and conclude with future developments. Baron and Kenny's (1986) approach to mediation analysis is one of the most cited articles in the past 30 years in all of social/personality psychology (Nosek et al, 2010) and is often accompanied by a z test or CI based on Sobel's standard error (Sobel, 1982). In brief, the Baron and Kenny approach (see Figure 2) involves a series of models: (a) predict the dependent variable from the independent variable to establish that a relationship exists, (b) predict the mediator from the independent variable to establish path a, and (c) predict the dependent variable from both the independent variable and mediator simultaneously to establish path b.…”
Section: Research-article2016mentioning
confidence: 99%